MODEL PELATIHAN ULANG (RETRAINING) PEKERJA PADA SUATU PERUSAHAAN BERDASARKAN PENILAIAN REKAN KERJA - Lestari, Dwi (Universitas Ahmad Dahlan, 2011)
In this paper, its discussed about the model re-training for workers in a company. To improve the quality of workers is usually held training (training) for workers, especially new workers or junior employees. However it is also the possibility of retraining for workers who decline spirit. The condition was one of the bases in formulating a model of retraining for workers in a company. Mathematical models for retraining discussed is a model re-training for workers based on an assessment of his colleagues. This model is shaped system of differential equations. In this model there are two equilibrium points namely the trivial equilibrium point and non-trivial equilibrium point. Local stability of the trivial equilibrium point of time fulfilled the conditions of the reproductive number is essentially less than one. This means that for a long time a good worker does not need to be a master so that workers do not re-training. Numerical simulation is given by taking the value of certain parameters that describe the changes in population size of each class of a time.